Impact of a varied set of stimuli on a suite of immunological parameters within peripheral blood mononuclear cells: toward a non-animal approach for assessing immune modulation by materials intended for human use - Cochrane, Stella; Rajagopal, Ramya; Sheffield, David; Stewart, Fay; Hathaway, Lindsay; Barnes, Nicholas M.; Qureshi, Omar; Gordon, John (Frontiers in Toxicology, 2024)
In toxicology steps are being taken towards more mechanism-focused and human relevant approaches to risk assessment, requiring new approaches and methods. Additionally, there is increasing emphasis by regulators on risk assessment of immunotoxicity. Here we present data from a peripheral blood mononuclear cell (PBMC) system whereby a varied set of stimuli, including those against the TCR and Toll-like receptors, enable readouts of cytokine and prostaglandin E2 (PGE2) production with monocyte, T cell and B cell viability, proliferation, and associated activation markers. In addition to results on the impact of the stimuli used, initial profiling data for a case study chemical, curcumin, is presented, illustrating how the system can be used to generate information on the impact of exogenous materials on three major constituent immune cell subsets for use in risk assessment and to direct follow-on studies. The different stimuli drove distinct responses, not only in relation to the 'quantity' of the response but also the 'quality'. Curcumin had a limited impact on the B cell parameters measured, with the stimuli used, and it was noted that in contrast to T cells where there was either no impact or a reduction in viability and proliferation with increasing concentration, for B cells there was a small but significant increase in both measurements at curcumin concentrations below 20 µM. Similarly, whilst expression of activation markers by T cells was reduced by the highest concentration of curcumin, they were increased in B cells. Curcumin only impacted the viability of stimulated monocytes at the highest concentration and had differential impact on different activation markers. Levels of all cytokines and PGE2 were reduced at higher concentrations. Whilst recognising the platform has certain limitations, it nevertheless enables assessment of healthy baseline monocyte, T-, and B-cell responses, and scrutiny of the impact of different stimuli to detect potential immune suppression or enhancement from exogenous materials. In the case of curcumin, a pattern of responses indicative of immune suppressive / anti-inflammatory effects was detected. It is an accessible, highly modifiable system that can be used to screen materials and guide further studies, providing a holistic, integrated picture of effects.